Germination and emergence of Astrocaryum murumuru Mart. under stratification in different temperature regimes - Jucimara Gonçalves dos Santos; Sidney Alberto do Nascimento Ferreira; Daniel Felipe de Oliveira Gentil (Journal of Seed Science)
ABSTRACT: Astrocaryum murumuru is a palm tree typical of Amazonian lowland areas (floodplains), whose seeds are exploited extractively for the manufacture of cosmetics. Germination of the species takes time, highlighting the need to develop techniques that shorten this process. Therefore, this research aimed to evaluate the germination and vigor of A. murumuru seeds, subjected to different thermal conditions of stratification. The experimental design adopted was completely randomized, with four treatments (different thermal conditions) and four replications. After drying the diaspores, extracting and soaking the seeds, these (with moisture content of 26.8%) were placed in double plastic bags containing vermiculite, moistened with water equivalent to 60% of their dry mass. They were then maintained under the following conditions: natural environment (27.8 ± 2.7 °C); oven with a temperature of 40 °C for 3 hours per day; oven with a temperature of 40 °C for 6 hours per day; and oven with a temperature of 40 °C for 9 hours a day. Stratification at a temperature of 40 °C/3 hours/day provides better germination performance and initial development of A. murumuru seedlings (51%), in addition to reducing remaining dormant (25%) and dead (24%) seeds.